Analiza športne vadbe različnih kategorij rekreativnih tekačev - Škof, Branko (Šport (Ljubljana), 2017)
The number of runners and running events both around the world and in Slovenia has escalated. Most people train by themselves, without expert guidance or medical monitoring. Therefore, formulating guidelines for healthy and effective recreational running training is an important and vital task of the sports profession. The purpose of the study was to identify the key characteristics of the sports training of recreational runners in different categories. The study encompassed 1,177 runners who were divided into four development categories based on their running achievements: i) beginner runners; ii) less experienced runners; iii) basic-recreational-level runners; and iv) high-recreational-level runners. The abovementioned groups differed substantially in all the observed quantitative and qualitative parameters of sports training. Faster runners train more and their training is higher in quality and more organised in terms of both health and running progress. The scope and contents of training of less experienced runners and beginner runners often fail to meet even the minimum criteria for healthy sports training. Their training is often not sufficiently comprehensive and deficient contents-wise. The results may be used as a good starting point for the formulation of guidelines for effective, healthy and safe running training.
Keywords: achievement; dosežek; recreation; rekreacija; running; sport; šport; tek; training; vadba